Pengaruh Bimbingan Kelompok Teknik Written terhadap Kecerdasan Naturalis Siswa - Nadia Wahyuni Thalib; Maryam Rahim; Irvan Usman (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2020)
As a reality, the vast majority of students, in particular, those at elementary school have yet to have awareness of the importance of nature preservation. This constitutes an indication of low naturalist intelligence of elementary school students. As an effort to cope with the problem, it requires solution, namely written technique group guidance. The problem of this research is whether or not written technique group guidance has an influence towards naturalist intelligence of elementary school students. The research uses a pre-experiment method with one group pretest and posttest design. The research samples are 15 people. The data collection uses questionnaire as the main technique. The data are analyzed by using t-test. Based on the research finding, it concludes that there is an influence of written technique group guidance towards naturalist intelligence of students at grade V of SDN No. 85 Kota Tengah of Gorontalo City. This conclusion is obtained from result of data analysis, which indicating value of tcount = -20,598, and at significance level of 0,05 (14), it obtains ttable = 2,98, which meant the tcount has been outside of acceptance area of H0. This means that the hypothesis which says, “there is influence of written technique group guidance towards naturalist intelligence of students at grade V of SDN 85 Kota Tengah of Gorontalo City, can be accepted. In other words, the written technique group guidance can increase the naturalist intelligence of students at grade V of SDN No.85 Kota Tengah of Gorontalo City. Based on the research finding, it is suggested that the guidance and counseling teachers should apply written technique group guidance as an effort to improve the naturalist intelligence of elementary school students.